Prenatal diagnostics of fetal abnormalities by ultrasound and color Doppler - (:unkn) unknown (My University, 2006)
There is no doubt that ultrasound provides many clinical advantages. It is shown that ultrasound enables the earlier detection of fetal malformations. Professionals expect from routine ultrasound objective information that cannot usually be obtained by clinical procedures. Parents seek reassurance about the absence of fetal congenital anomalies and overall fetal health. Therefore, people view routine ultrasound as a part of obstetrical care, capable of filling important gaps by delivering much key information for improving obstetrical practice. Fetal anomalies screening requires higher education and qualifications than usual obstetrical ultrasound. In this paper we are summarizing the fetal anomalies that can be detected and evaluated by ultrasound and color Doppler by presenting some examples of our original cases with fetal abnormality. Progressive improvements in ultrasound equipment have permitted within the field of prenatal diagnosis of structural fetal anomalies to obtain a very high sensitivity and specificity, with utilization of high resolution equip-ment and an expert ultrasonographist in fetal dysmorphology.
Keywords: Color Doppler; Fetal abnormalities; Prenatal diagnosis; Ultrasound